2018
DOI: 10.1161/jaha.118.009820
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid in Adipose Tissue and Development of Ischemic Stroke: A Danish Case‐Cohort Study

Abstract: BackgroundWe investigated the association between the content of linoleic acid in adipose tissue, a biomarker of long‐term intake of linoleic acid, and the risk of ischemic stroke and its subtypes.Methods and ResultsThe Danish cohort study Diet, Cancer and Health included 57 053 patients aged 50 to 65 years at enrollment. All participants had an adipose tissue biopsy performed at enrollment, while information on ischemic stroke during follow‐up was obtained from the Danish National Patient Register. Stroke dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Observational studies of the association between individual FAs and ischemic stroke, including large-artery stroke, are relatively limited and the findings are conflicting, possibly because of small sample sizes of some studies and residual confounding. Most but not all studies support that moderate or high ALA [28] and LA [29,30] and low SA [31,32] exposure is associated with lower risk of ischemic stroke, which is in line with our results, although our findings for SA were not significant. A large Danish cohort study reported a significant inverse association between the content of LA in adipose tissue and risk of large-artery stroke [30].…”
Section: Plasma Fas and Ischemic Strokesupporting
confidence: 91%
See 2 more Smart Citations
“…Observational studies of the association between individual FAs and ischemic stroke, including large-artery stroke, are relatively limited and the findings are conflicting, possibly because of small sample sizes of some studies and residual confounding. Most but not all studies support that moderate or high ALA [28] and LA [29,30] and low SA [31,32] exposure is associated with lower risk of ischemic stroke, which is in line with our results, although our findings for SA were not significant. A large Danish cohort study reported a significant inverse association between the content of LA in adipose tissue and risk of large-artery stroke [30].…”
Section: Plasma Fas and Ischemic Strokesupporting
confidence: 91%
“…Most but not all studies support that moderate or high ALA [28] and LA [29,30] and low SA [31,32] exposure is associated with lower risk of ischemic stroke, which is in line with our results, although our findings for SA were not significant. A large Danish cohort study reported a significant inverse association between the content of LA in adipose tissue and risk of large-artery stroke [30]. However, circulating ALA levels were not significantly associated with ischemic stroke in smaller cohorts of Swedish [33] and U.S. [34] adults.…”
Section: Plasma Fas and Ischemic Strokesupporting
confidence: 91%
See 1 more Smart Citation
“…Stroke was defined as an acute disturbance of focal or global cerebral function with symptoms lasting more than 24 h. By linkage to the Danish National Patient Register possible stroke cases within the cohort were identified according to ICD-8 discharge codes 430, 431, 433, 434, 436.01, or 436.90, or ICD-10 discharge codes I60, I61, I63 or I64. Medical records and hospital discharge letters were reviewed, and diagnoses validated and characterized on the basis of clinical appearance, computed tomography, magnetic resonance imaging scan, autopsy records, spinal fluid examination and other relevant information [ 18 , 19 ]. All ischemic stroke cases were subclassified according to The Trial of Org 10172 in Acute Stroke Treatment (TOAST) classification [ 20 ] and the subtypes included large artery atherosclerosis, cardioembolism, small-vessel occlusion, stroke of other etiology, and stroke of undetermined etiology.…”
Section: Methodsmentioning
confidence: 99%
“…Several prospective biomarker studies have supported that circulating or adipose tissue content of LA may be associated with a lower risk of ischemic stroke although results have not been consistent [23,31,32,37,38,39,40,49] (Table 7). A previous study by Iso et al suggested a lower odds of total ischemic stroke and lacunar infarctions per 1 SD increase in LA content in serum [31].…”
Section: La and Ischemic Strokementioning
confidence: 99%